Compensação tributária: análise crítica às limitações previstas no § 3º do art. 74 da Lei Federal nº 9.430/1996 - Alves, Taciana Stanislau Afonso Bradley (2010)
The purpose of this work is to analyze the tax offsetting institute as a mechanism of extinguishment of the tax obligation of the taxpayer and his debit before the tax authorities. The offsetting rule prescribes the calculation relationship, extinguishing the tax obligation of the taxpayer and his debit relation with the tax authorities. In the end, the purpose is to demonstrate in the Federal tax legislation that regulates the offsetting institute, the restrictions imposed by the ordinary law maker to the administrative proceeding of offsetting in the hypothesis of no-declared offsetting. Those restrictions should not prevail because they are against the due process of law, guaranteed by the Federal Constitution. The method adopted is the constructivism logic-semantic, approaching the law as a communicational process that constitutes, modifies and extinguishes itself through a unique legal language which is the language of the proofs admitted in law